Twelve Views from the Distance - Takahashi, Mutsuo, 1937- (Book collections on Project MUSE., 2012)
From one of the foremost poets in contemporary Japan comes this entrancing memoir that traces a boy's childhood and its intersection with the rise of the Japanese empire and World War II. Originally published in 1970, this translation is the first available in English. In twelve chapters that visit and revisit critical points in his boyhood, Twelve Views from the Distance presents a vanished time and place through the eyes of an accomplished poet. Recounting memories from his youth, Mutsuo Takahashi captures the full range of his internal life as a boy, shifting between hi.